Photocatalytic Antibacterial Performance of Glass Fibers Thin Film Coated with N-Doped SnO2/TiO2 - Peerawas Kongsong; Lek Sikong; Sutham Niyomwas; Vishnu Rachpech (The Scientific World Journal)
Both N-doped and undoped thin films of 3SnO2/TiO2 composite were prepared, by sol-gel and dip-coating methods, and then calcined at 600°C for 2 hours. The films were characterized by FTIR, XRD, UV-Vis, SEM, and XPS, and their photocatalytic activities to degrade methylene blue in solution were determined, expecting these activities to correlate with the inactivation of bacteria, which was confirmed. The doped and undoped films were tested for activities against Gram-negative Escherichia coli (E. coli) and Salmonella typhi (S. typhi), and Gram-positive Staphylococcus aureus (S. aureus). The effects of doping on these composite films included reduced energy band gap, high crystallinity of anatase phase, and small crystallite size as well as increased photocatalytic activity and water disinfection efficiency.